Leaching Behavior of Gold in Ammoniacal Solutions in the Presence of Bromine as an Oxidant - Peter Mam-soo Kim; Kenneth N. Han (Society for Mining, Metallurgy & Exploration, 2005)
The extraction behavior of gold in ammoniacal solutions in the presence of bromine as an oxidant has been studied. The effect of concentration of ammonia, bromine, and pH of the solution on the rate of dissolution of gold was investigated. The dissolution behavior has been analyzed using electrochemical method, and its results were compared with direct leaching tests using gold powder. The overall dissolution of gold in ammoniacal solution containing bromine was found be affected significantly by pH of the solution and the concentration of bromine. The rate expression found in this study has the following form.